Legal Protection of Business Actors in the Concept of Business to Business - Astawa, I Ketut; Saputro, Bambang (Jurnal Independent, 2023)
AbstractThe purpose of this study is to examine how business actors are legally protected when conducting electronic commerce. This research uses a normative legal approach through conceptual and normative approaches, where this study is connected with relevant legal principles and laws and regulations. The nature of analytical descriptive research was used in this study. The findings of this study include legal protection in the concept of business-to-business e-commerce, including contract terms, electronic evidence, and obligations of the parties, as well as legal protection in e-commerce contracts and legal protection. In a legal setting, each party is subject to obligations and rights. Because transactions in the practice of electronic trading usually involve two parties. Every party to the transaction, including the seller and the buyer, has obligations and rights that must be exercised consciously. This is because there is no legal protection for online buying and selling transactions. The government, which acts as a regulator, is currently reviewing Law No. 19 of 2016 in the preparation of electronic information and transactions and the Consumer Protection Law.